Caligula-Christ: Preliminary Study of a Parallel - Lorene M. Birden (Studies in 20th & 21st Century Literature, 2010)
Caligula, at the very beginning of the Albert Camus play, conceives a very ambitious project; to surpass the gods and take their place in his empire, in order to decree impossibility. Camus has, however, gone a step further in developing the god-image of his main character through the incorporation of much Christian imagery into the scenes. This aspect of the play seems not to have been noticed by Camus scholars; there is no in-depth study of the use of this imagery. However, Camus scholar Patricia Johnson and the members of the Société des études camusiennes have noted the usefulness of the analysis presented here and the absence of it in previous research. This study, designated as “preliminary,” attempts to prompt further analyses of the question and offers different approaches. It proceeds by intertextual study of Caligula and the gospels (here referred to in Revised Standard Version) and brings out aspects of the emperor’s intentions that expose a combination of perversion and similarity in relation to deity. It briefly outlines the sources of this parallel and the reasons for creating it, then details the parallels that show first the reversal of the image of Jesus, then the striking consonance. It ends with interpretations of the parallels and concludes with commentaries on the use of irony to create them.
Keywords: Caligula; Christ; Albert Camus; play; Christian imagery; Patricia Johnson; Société des études camusiennes; irony